Rasionalisasi Bantuan Operasional Sekolah (BOS) Pada Pendidikan Keagamaan Islam Formal - Idam Mustofa (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2017)
Government funding for formal Islamic religious education in the form of BOS is increasing. With increased funding from the government and government policies, people still have to be willing to make their contributions. By using the normative-prescriptive approach this study focuses on analyzing the preferences of BOS use in formal Islamic religious education so that it can be a rational choice in order to meet its financing. From the results of the discussion, the Government is obliged to fulfill the rights of formal Islamic religious education as applied to other formal madrasas, at the same time formal Islamic religious education is also obliged to carry out its functions as a religious producer who is vertically responsible to the Ministry of Religion, and relates horizontally with the community. Although on the one hand there is BOS funds (fix costs) as a minimum need and routine funds for the needs of formal Islamic religious education, each organizer must remain rational by maintaining public accountability. The SBM model is a model that can be chosen to encourage more accountable BOS management